On the nature of flux variations of trapped particles associated with sudden commencement and sudden impulse at synchronous orbit - Tsunomura, Satoru; Kuwashima, Masayuki (1984)
P(論文) Morphology and mechanism of the flux variation of energetic particles associated with sudden commencements and sudden impulses are examined on the basis of the observations of high-energy particles measured by the SEM on board the GMS and GOES series, during the period from February 1978 to December 1978. The events are divided into two types morphologically, one is a step-like variation and the other is a pulse-like one. The former shows characteristics of the trapped particles but the latter does not significantly. From the analysis of the former type ones, a weak dependence on △H (amplitude of SC or SI) due to betatron acceleration is recognized for the rate of variation of particle flux. The variation of flux is also affected by the level of the flux before the SC or SI, and in some cases the effect surpasses that of acceleration of particles. departmental bulletin paper